Demosthenes' "On the Crown" : Rhetorical Perspectives - Demosthenes (Landmarks in Rhetoric and Public Address Ser, 2016)
Cover -- Title Page -- Copyright -- Contents -- Introduction -- Part One: Demosthenes and His Greatest Speech -- 1. Demosthenes and His Times -- 2. Aeschines' Speech Against Ctesiphon: An Abstract -- 3. Demosthenes' Oration "On the Crown": A Translation -- Part Two: Rhetorical Evaluations -- 4. A Structural Analysis of the Speech "On the Crown" -- 5. Ēthos in "On the Crown" -- 6. Crafting Nostalgia: Pathos in "On the Crown" -- 7. On the Deinos Logos of "On the Crown" -- 8. Demosthenes' Style: Lexis in "On the Crown" -- Epilogue -- Select Bibliography -- Contributors -- Index -- Landmarks in Rhetoric and Public Address: Also in this series -- Back Cover.